2014
DOI: 10.1007/s12185-014-1688-6
|View full text |Cite
|
Sign up to set email alerts
|

Thrombocytopenia in pregnancy: do the time of diagnosis and delivery route affect pregnancy outcome in parturients with idiopathic thrombocytopenic purpura?

Abstract: The objective of this study was to investigate the determining effects of diagnosis time on pregnancy outcomes in a population of pregnant women with idiopathic thrombocytopenic purpura (ITP). Records of all the pregnant women with thrombocytopenia were evaluated. Those with a confirmed diagnosis of ITP were included in the study. Main outcome measures were antenatal thrombocyte count, postpartum haemorrhage rate, and route of delivery. Foetal outcomes such as foetal thrombocyte count, haemorrhage, and birth w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
28
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(36 citation statements)
references
References 8 publications
4
28
0
3
Order By: Relevance
“…11 The incidence of fetal thrombocytopenia was higher in the studies of Yuce et al (14%), Yassaee et al (10.50%) and Bhat et al (36.10%) and difference were statistically significant. 23,28 [9][10][11]14,21 In the present study HELLP syndrome was seen in 1.50% of the thrombocytopenic women which was statistically similar to the study by Turgot et al (1.14%), Habas et al (0.37%) and Vyas et al (4.08%). 9,18,19,30 Whereas studies by Parnas et al and Onisai et al showed HELLP syndrome in 12.06% and 9.52% women respectively, which was higher than our study.…”
Section: 17supporting
confidence: 90%
See 2 more Smart Citations
“…11 The incidence of fetal thrombocytopenia was higher in the studies of Yuce et al (14%), Yassaee et al (10.50%) and Bhat et al (36.10%) and difference were statistically significant. 23,28 [9][10][11]14,21 In the present study HELLP syndrome was seen in 1.50% of the thrombocytopenic women which was statistically similar to the study by Turgot et al (1.14%), Habas et al (0.37%) and Vyas et al (4.08%). 9,18,19,30 Whereas studies by Parnas et al and Onisai et al showed HELLP syndrome in 12.06% and 9.52% women respectively, which was higher than our study.…”
Section: 17supporting
confidence: 90%
“…9,11,20 Whereas the incidence of LSCS was higher in the studies conducted by Pafumi et al (55%) and Yuce et al (56%). 28,31 In the present study 4.60% subjects required blood transfusion. However, the need for blood transfusion was higher in the studies by Parnas et al (16.60%), Borna et al (26.20%), Yuce et al (10%) and Dwivedi et al (9.0%).…”
mentioning
confidence: 45%
See 1 more Smart Citation
“…Of the 25% of women who underwent cesarean section, thrombocytopenia was cited as the indication in only 7% of deliveries (n = 2) [9]. In several retrospective studies, hemorrhagic complications were uncommon in the mother or neonate and were not related to the mode delivery or maternal platelet count [9,[32][33][34][35].…”
Section: Deliverymentioning
confidence: 99%
“…Gestational thrombocytopenia, which usually occurs in the midsecond to third trimester and which is a mild form with platelet counts more than 70x10 3 /μL, constitutes 70-80% of cases (1,5). ITP, which is an autoimmune disease with autoantibodies against the platelet membrane causing platelet destruction in the reticuloendothelial system, must be considered in the differential diagnosis.…”
Section: Introductionmentioning
confidence: 99%